2011
DOI: 10.1097/nmd.0b013e31821ccb07
|View full text |Cite
|
Sign up to set email alerts
|

Coping Styles in Carers of People With Recent and Long-Term Psychosis

Abstract: Avoidant coping is associated with distress in carers of people with psychosis. We hypothesized that this form of coping would abate as carers adapt their coping strategies in the course of the illness. One hundred and forty-one carers of two groups of patients, with recent onset and longer established psychosis, respectively, completed self-report measures of coping and general distress. We found that avoidant coping strategies were associated with carer distress but not with duration of illness. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
(15 reference statements)
2
27
1
Order By: Relevance
“…This corresponds with findings by Montgomery and Williams (2001) who reported that length of care in carers of the elderly was not an independent predictor of carer well-being. This would also support Onwumere et al (2011) who suggested that carer well-being was influenced more by the coping strategy used rather than the duration of care. The well-being of carers of people with SEED was not significantly different.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This corresponds with findings by Montgomery and Williams (2001) who reported that length of care in carers of the elderly was not an independent predictor of carer well-being. This would also support Onwumere et al (2011) who suggested that carer well-being was influenced more by the coping strategy used rather than the duration of care. The well-being of carers of people with SEED was not significantly different.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, in the psychosis literature, carers of people with first episode psychosis experienced high levels of burnout early on in their caregiving role (Onwumere et al, 2015). However, earlier research by Kuiper's team suggested that carer well-being may not be nfluenced by illness duration but avoidant carer coping strategies, which were detrimental (Onwumere et al, 2011). To date, there is limited information on illness duration in carers of people with ED, perhaps due to a lack of longitudinal studies (Gonzalez et al, 2012).…”
mentioning
confidence: 96%
“…In addition, the study adjusted for caregiver and patient characteristics and included two caregivers per patient in a multilevel analysis. The inclusion of two caregivers possibly explains why we have more male participants compared with other studies on caregiver distress as most studies include only one significant other which typically is the mother [49,50]. With these limitations and strengths in mind, the current study provides further support for the stress-appraisal coping theory and the cognitive model of caregiving in families with first-episode psychosis.…”
Section: Limitations Strengths and Clinical Implicationsmentioning
confidence: 60%
“…Emotional and physical burnout recorded in caregivers has been equivalent to levels observed in psychiatric staff 16. Caregiver distress is associated with less adaptive coping styles characterized by behavioural and cognitive avoidance 17,18…”
mentioning
confidence: 92%